2021
DOI: 10.1007/s00464-020-08261-5
|View full text |Cite
|
Sign up to set email alerts
|

A knowledge gap unmasked: viral transmission in surgical smoke: a systematic review

Abstract: Background Concerns regarding the aerosolized transmission of SARS-CoV-2 via SS have caused significant apprehension among surgeons related to the use of minimally invasive surgery (MIS) during the COVID19 pandemic. While a limited number of studies have previously demonstrated the presence of viral material in SS, no comprehensive systematic review exists on the subject of viral transmission in SS. Methods A systematic review of the literature was conducted as per PRISMA guidelines. MEDLINE, EMBASE, and CENTR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 68 publications
0
11
0
Order By: Relevance
“…A recent meta-analysis showed that operating room personnel who participated in ablation procedures, such as laser irradiation, LEEP and cryosurgery, were at risk for HPV transmission [24]. Furthermore, a systematic review conducted by Connal et al [25] identified the risk of viral transmission in surgical smoke, and HPV was the only virus that demonstrated clinical infection in humans exposed to surgical smoke, while human immunodeficiency virus, hepatitis B virus and varicella zoster virus tended not to be transmissible. In the present study, we discovered the presence of HPV DNA in surgical smoke and matched HPV genotypes to the corresponding cervical cancer mouse xenograft models.…”
Section: Discussionmentioning
confidence: 99%
“…A recent meta-analysis showed that operating room personnel who participated in ablation procedures, such as laser irradiation, LEEP and cryosurgery, were at risk for HPV transmission [24]. Furthermore, a systematic review conducted by Connal et al [25] identified the risk of viral transmission in surgical smoke, and HPV was the only virus that demonstrated clinical infection in humans exposed to surgical smoke, while human immunodeficiency virus, hepatitis B virus and varicella zoster virus tended not to be transmissible. In the present study, we discovered the presence of HPV DNA in surgical smoke and matched HPV genotypes to the corresponding cervical cancer mouse xenograft models.…”
Section: Discussionmentioning
confidence: 99%
“…Usually, smaller PM can travel longer distances and trigger more chemical effects related to surgical smoke, while larger PM may have a higher infection risk. Interestingly, although the size of PM generated by electrosurgical knives is smaller than that generated by ultrasonic devices, the latter devices produce more PM than the former ones [27]. Hence, given the complex in uences of energy-generating devices on surgical smoke, more indepth investigation is necessary.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the precautions taken in operating rooms [5], which naturally contain many stress factors, problems related to surgical smoke and detection of viruses in surgical smoke [9,[12][13][14] can be an additional source of stress for the healthcare personnel working in these units; moreover, it raises the concern that the SARS-CoV-2 virus may be transmitted through surgical smoke [9,28].…”
Section: Discussionmentioning
confidence: 99%